2020
DOI: 10.1002/ajmg.a.61879
|View full text |Cite
|
Sign up to set email alerts
|

Recommended measures for the efficient care of patients with genetic disorders during the COVID‐19 pandemic in low and middle income countries

Abstract: The coronavirus disease 2019 (COVID-19) emerged in early 2020 and since, has brought about tremendous cost to economies and healthcare systems universally. Reports of pediatric patients with inherited conditions and COVID-19 infections are emerging. Specific risks for morbidity and mortality that this pandemic carries for different categories of genetic disorders are still mostly unknown. Thus, there are no specific recommendations for the diagnosis, management, and treatment of patients with genetic disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…In summary, this correspondence adds to the evolving knowledge of management of genetic disorders by providing real‐world data on the hospital care of inherited cardiomyopathies in Germany during the Covid‐19 pandemic and complements the previous call for more data published here (Hamad et al, 2020).…”
Section: Figuresupporting
confidence: 63%
See 1 more Smart Citation
“…In summary, this correspondence adds to the evolving knowledge of management of genetic disorders by providing real‐world data on the hospital care of inherited cardiomyopathies in Germany during the Covid‐19 pandemic and complements the previous call for more data published here (Hamad et al, 2020).…”
Section: Figuresupporting
confidence: 63%
“…Thus, a recent paper in this journal (Hamad et al, 2020) not only recommended measures for the efficient care of patients with genetic disorders during the pandemic but suggested also to study the impact of Covid‐19 on diagnosis, management, and treatment of genetic disorders. Although this paper focused on low‐ and middle‐income countries, we believe that due to scarcity of data the latter applies also to upper–middle‐income countries.…”
Section: Figurementioning
confidence: 99%
“…Over the years, with improved awareness and advocacy, some patients with lysosomal storage disorders (LSD) receive intravenous infusions of enzyme replacement therapy (ERT) [3]. This management and associated multidisciplinary care are ordinarily challenging with significant impact on the family [4]. With the strict nationwide lockdown, we hypothesized that the pandemic brought new challenges for these patients.…”
Section: Challenges In Chronic Genetic Disorders: Lessons From the Covid-19 Pandemicmentioning
confidence: 99%
“…Waist circumference is a widely accepted and practical tool for community screening of obesity [2]. However, certain concerns have been raised over the cutoff being used while utilizing waist circumference as a predictor of metabolic syndrome [3,4]. We explored the suitability of lower waist circumference cutoff…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] During the novel coronavirus (COVID-19) outbreak, the specific risks for patients with genetic disorders were not fully disclosed; however, available data indicated that they have a more severe course of infection compared to the general population requiring intensive care support. [3] We described the critical care management of a 20-year-old patient with ROHHAD syndrome presenting with COVID-19 and discussed the clinical challenges. The patient was admitted to the emergency department with complaints of shortness of breath and fever.…”
mentioning
confidence: 99%